The Effect of Family Resilience towards Household Disaster Preparedness in Coastal Coast District of Sumur, Banten. Issue 1 (March 2020) - Gumelar, G; Akbar, Z; Suryaratri, R D; Erchanis, H; Wahyuni, L D
Abstract: The tsunami of Sunda Strait that struck Banten and Lampung on Saturday, December 22, 2018 had been claimed many lives, especially in three most affected areas, Pandeglang, Banten, and South Lampung. To minimise the casualty, disaster preparedness program needs to be initiated from the smallest element, such as family or household. Family members need to understand the steps that are needed to be taken for life survival and property protection during the disaster situations. This research was conducted to determine the effect of family resilience towards household disaster preparedness in response to disasters in Sumur District, Banten. The participants of this study were 174 respondents from the family affected by the tsunami. Disaster Preparedness Measured by LIPI-UNESCO/ISDR Instrument and the instrument for Family Resilience by Walsh Family Resilience Framework – Questionnaire were used in this research. The finding shows that family resilience had a significant contribution to the household disaster preparedness by 27.1%. Furthermore, this study also found a high level of household disaster preparedness among families in Sumur District. However, household disaster preparedness and family resilience need to be socialized continuously due to many family members do not have adequate knowledge about disaster preparedness.